Berlin & Berlin Stadtplanung nach dem Mauerfall - Kunst, Friedemann (De Gruyter, 2021)
After the Wall came down, Berlin was faced with unprecedented city planning tasks. The partition of the city needed to be remedied, and ideas for the as-yet uncertain future needed to be developed and implemented within an extremely short time. Fifteen of the planners from East and West Berlin responsible look back on the concepts that were created, how the decision processes were organized, what conflicts were resolved (or not), and whether key decisions have stood the test of time. In interviews about this challenging period of transformation, eyewitness accounts provide a lively record of the mood during the first five years of reunification and illustrate contemporary contexts and backgrounds. Images of urban developments, some previously unpublished, offer a new perspective on the Berlin of the early nineties. With contributions by Dorothee Dubrau, Bruno Flierl, Volker Hassemer, Bernd Hunger, Urs Kohlbrenner, Ulla Luther, and others as well as photos of the city by E.-J. Ouwerkerk.